UNLOCKING THE FACTS BEHIND NURSING STUDENT CLINICAL PRACTICES: CHALLENGES DURING THE COVID-19 OUTBREAK - Ira Kusumawaty; Yunike; Devi Mediarti; Yeni Elviani (Bajang Institute, 2022)
The Covid-19 pandemic increases the complexity of implementing nursing clinic practices fluctuating. Clinical-stage learning outcomes are strongly influenced by online learning methods at the academic stage which preparing students' knowledge, skills, and attitudes before treating patients positively. In fact, preparation in academic stage is feared, because it can affect the formation of student professionalism. Many studies have revealed students' problems during clinical education, but information relating to student experience during clinical nursing practice is still very limited. This research aims to identify and explore the experience of nursing students in caring for Covid-19 patients during the nursing clinic. Qualitative research with phenomenological approaches and data collection using in-depth interviews have been implemented in this study. Participants are nursing students who have participated in nursing clinic practices during the Covid-19 pandemic, numbering 14 participants. Participants ‘exposure was done with purposive sampling techniques. Researchers are research instruments using in-depth interview guidelines and voice recording devices. Trustworthiness efforts are made by conducting peer debriefing and member checking. The data were analyzed with Colaizzi's method and resulted in three main themes: gaining valuable experience during treatment, as a role model, and empathy for patients.